Neural tube expression of pituitary adenylate cyclase-activating peptide (PACAP) and receptor: Potential role in patterning and neurogenesis - Waschek, James A. (The National Academy of Sciences, 1998)
Neural tube patterning in vertebrates is controlled in part by locally secreted factors that act in a paracrine manner on nearby cells to regulate proliferation and gene expression. We show here by in situ hybridization that genes for the neuropeptide pituitary adenylate cyclase-activating peptide (PACAP) and one of its high-affinity receptors (PAC(1)) are widely expressed in the mouse neural tube on embryonic day (E) 10.5. Transcripts for the ligand are present in differentiating neurons in much of the neural tube, whereas the receptor gene is expressed in the underlying ventricular zone, most prominently in the alar region and floor plate. PACAP potently increased cAMP levels more than 20-fold in cultured E10.5 hindbrain neuroepithelial cells, suggesting that PACAP activates protein kinase A (PKA) in the neural tube and might act in the process of patterning. Consistent with this possibility, PACAP down-regulated expression of the sonic hedgehog- and PKA-dependent target gene gli-1 in cultured neuroepithelial cells, concomitant with a decrease in DNA synthesis. PACAP is thus an early inducer of cAMP levels in the embryo and may act in the neural tube during patterning to control cell proliferation and gene expression.